Peningkatan Pemahaman Siswa Tentang Kenampakan Alam Melalui Metode Diskusi Pada Siswa Kelas IV Semester 1 SDN 1 Bicak Todanan-Blora Tahun 2015/2016 - Handayani, Dwi, Drs. Suwarno, SH., M. Pd (2015)
This study was motivated by the lack of understanding of students in understanding the natural appearance. The purpose of this research is to improve learning outcomes in understanding the natural appearance in the fourth grade students at SDN 1 Bicak District of Todanan Blora. This research was conducted using Action Research (PTK) by the method of discussion.This research was conducted in two cycles with 2 meeting. Subjects were fourth grade students of SD Negeri 1 Bicak District of todanan Blora academic year 2015/2016 a total of 11 students. Managing data in this study by analyzing data qualitatively. Learning outcomes as quantitative data obtained from the results of group work and individual evaluation of the test results to see an increase in students' understanding of the concept of the natural appearance of the material. Secondary data include data on students' understanding of the learning outcomes of students, pratindakan, lesson plan, syllabus and curriculum derived from the documents held by teachers and school. Data collected through the practice tests, observations, consider the study and observation. To test the validity of the data is done by triangulation. From the analysis of the data found that student learning outcomes before action is held three students (27.27%) thoroughly studied and 8 students (72.72%) has not been thoroughly studied. In the first cycle 5 (45.45%) students have thoroughly studied and 6 students (54.54%) has not been thoroughly studied. In the second cycle reaches 99% passing grade is 11 students have been thoroughly studied. Beradasarkan the data above, shows that the improvement of learning social studies subject of natural features has produced a satisfactory value, thus the improvement of learning has been completed.